Diversity of Butterfly Food Types and Sources in Lombok Permaculture - Indriyatno; Gunadi, Putu Eka (PT FORMOSA CENDEKIA GLOBAL, 2025)
Butterflies are insects that live in various ecosystems. Healthy ecosystems tend to have a high diversity of butterfly species, due to the diversity of plants as food sources and breeding places. Permaculture, as a sustainable agricultural system, has three basic ethics that focus on caring for the earth, caring for people, and sharing fairly. This ethic provides space for other living creatures, including butterflies, to develop and maintain ecosystem balance. The aim of this research is to determine the type of butterfly, diversity, abundance, richness, and types of host plants in the caterpillar phase. The method used in this research is purposive exploration, with data analysis using the Shannon-Wienner diversity index (H') and evenness index to assess the diversity and stability of the ecosystem. The results of the research show that there are 85 types of plants that make up Lombok Permaculture, with 25 types of host plants and 35 types of butterflies. The value of the Shannon-Wienner diversity index is relatively low, namely 0.82, which indicates that the diversity of butterfly species is still limited. The evenness index is also relatively low at 0.23, which indicates the stability of an ecosystem that is still vulnerable to disturbance. However, the richness index shows a fairly high value, namely 7.12, which means that the area has many species